2022
DOI: 10.2196/preprints.34742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Dermatology Content by Top Influencers on Twitter and Their Academic Impact: Cross-Sectional Study (Preprint)

Abstract: UNSTRUCTURED -

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…22 Research has also identified that women constitute a minority of members of journal editorial boards. 23,24 Of the 87 dermatology journals examined in one study, women occupied 18% of editor-in-chief positions, 36% of deputy editor roles, 22% of overall editorial board positions and 22% of other board roles. 23 In another study, women made up 37% of editorial board positions of the top 20 dermatology journals.…”
Section: Editor and Editorial Board Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Research has also identified that women constitute a minority of members of journal editorial boards. 23,24 Of the 87 dermatology journals examined in one study, women occupied 18% of editor-in-chief positions, 36% of deputy editor roles, 22% of overall editorial board positions and 22% of other board roles. 23 In another study, women made up 37% of editorial board positions of the top 20 dermatology journals.…”
Section: Editor and Editorial Board Rolesmentioning
confidence: 99%
“…23 In another study, women made up 37% of editorial board positions of the top 20 dermatology journals. 24…”
Section: Editor and Editorial Board Rolesmentioning
confidence: 99%
“…One review study of all dermatology journals found that only 22% of editorial board members were women [8]. Another recent analysis exploring gender parity of the top 20 dermatology journals' editorial boards found that women comprised a median of 33.4% (IQR 27.2%-46.9%) of their editorial boards [9]. Only in 4 of the 20 top journals did women comprise a >50% average of the editorial board [9], even though a 2018 report by the Association of American Medical Colleges found that 51% of full-time, faculty dermatologists are women [10].…”
mentioning
confidence: 99%
“…Another recent analysis exploring gender parity of the top 20 dermatology journals' editorial boards found that women comprised a median of 33.4% (IQR 27.2%-46.9%) of their editorial boards [9]. Only in 4 of the 20 top journals did women comprise a >50% average of the editorial board [9], even though a 2018 report by the Association of American Medical Colleges found that 51% of full-time, faculty dermatologists are women [10]. Among the top 20 journals, 75% had a male editor-in-chief [9] and 81% of all dermatology journals had a male editor-in-chief [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation